The Impact of Air Pollution on Hospitalization for Cardiovascular and Cerebrovascular Disease in Shenyang, China - Qingquan REN; Shuyin LI; Chunling XIAO; Jiazhi ZHANG; Hong LIN; Shuai WANG (Tehran University of Medical Sciences, 2020)
Background: The aim of this study was to investigate the overall impact of PM2.5, PM10, NO2, SO2, CO, and O3 on the admission of cardiovascular and cerebrovascular disease. Methods: We collected data on cardiovascular and cerebrovascular disease admissions from two hospitals in Shenyang Liaoning, China from Jan 2014 to Dec 2017, as well as daily measurements of six pollutants at 11 sites in Shenyang. The generalized additive model was used to assess the association between daily contaminants and admission to cardiovascular and cerebrovascular disease. Results: The single-contamination model showed a significant correlation between NO2, O3, PM10 and cardiovascular and cerebrovascular diseases at lag0 day. Air pollutants had lag effects on different gender groups. Excess relative risks (ERs) associated with a 10 μg/m3 increase were 1.522(1.057, 1.988) on lag02 for NO2, 0.547% (0.367%, 0.728%), 0.133% (0.061%, 0.205%) on lag3 for O3 and PM10. The dual pollutant model showed that the effects of NO2, O3, and PM10 after adjusting the influence of other pollutants were still statistically significant. Conclusion: Short-term exposure to ambient air pollution (NO2, O3, and PM10) may be associated with an increased risk of daily cardiovascular and cerebrovascular admission, which may provide reliable evidence for further understanding of the potential adverse effects of air pollution on cardiovascular and cerebrovascular diseases.